Penentuan Prioritas Rehabilitasi dan Rekontruksi Pasca Bencana Alam dengan Metode Multi Attribute Utility Theory (MAUT) (Studi Kasus : Provinsi Jawa Timur) - Megamas Hariyati; Yuliani Puji Astuti (Universitas Negeri Surabaya, 2020)
Rehabilitation and reconstruction was an activity in a region that had been affected by natural disaster. Rehabilitation and reconstruction is done in accordance with regulation created according to rehabilitation and reconstruction guidline disaster. Standard provision enacted with rehabilitation and reconstruction priority identification are needed because it is necessary to make the normalization of life and optimize life toward a region after natural disaster. In this study using the MAUT (Multi Attribute Utility Theory) method to determine priorities for rehabilitation and reconstruction after natural disaster. The result of the MAUT calculation method obtained recommendations regarding the determination of priorities for post-natural disaster rehabilitation and reconstruction in the area of ​​East Java Province based on the data of 3 years recently obtained a rating (0,145027967) as the highest assessor is the area affected by natural disaster namely Sidoarjo in 2017. (0,1609600) as the highest assessor is the area that struck natural disaster namely Kediri in 2018 (0,149155) as the highest assessor is the area affected by natural disaster that Pacitan in 2019. Keywords: Rehabilitation and Reconstruction, Java Province, MAUT, Decision Support Sistem